Market Anticipations of Government Policies and the Price of Gold - Salant, Stephen W.; Henderson, Dale W. (Journal of Political Economy, 1978)
This paper is an analysis of the effects of anticipations of government sales policies on the real price of gold. Although the risk of a future government gold auction depresses the price, it also causes the price to rise in percentage terms faster than the real rate of interest and at an increasing rate. Even risk-neutral investors require this rate of return as inducement to hold gold in the face of the asymmetric risk of a price collapse. Announcements making a government auction more probable cause a sudden drop in the price. Government attempts to peg the price or to defend a price ceiling with sales from its stockpile must result eventually in a sudden attack by speculators.